Ophthalmological monitoring in patients with hypertension and coronary heart disease - L.K. Moshetova; I.V. Vorobyeva; A. Dgebuadze; O.D. Ostroumova; A.V. Arablinskiy; E.P. Delver; A.A. Belogurov (РМЖ "Клиническая офтальмология")
L.K. Moshetova1, I.V. Vorobyeva1, A. Dgebuadze1, O.D. Ostroumova1,2, A.V. Arablinskiy1,2, E.P. Delver3, A.A. Belogurov3 1Russian Medical Academy of Continuous Professional Education, Moscow,  Russian Federation 2S.P. Botkin City Clinical Hospital, 5, 2nd Botkinskiy passage, Moscow, Russian Federation 3National Medical Research Center of Cardiology, Moscow, Russian Federation Aim: to study ophthalmological clinical functional parameters in patients with hypertension and coronary heart disease (CHD) with coronary artery stenosis. Patients and Methods: 30 patients (58 eyes) with hypertension and CHD with coronary artery stenosis (group A) and 30 healthy controls (60 eyes, group B) were examined. Best-corrected visual acuity (BCVA), macular sensitivity (MS) assessed by MAIA microperimetry, central macular thickness (CMT), foveal avascular zone (FAZ) area, vessel density of superficial capillary plexus (SCP VD) and deep capillary plexus (DCP VD) and choriocapillaris measured by optical coherence tomography angiography (OCTA) were evaluated. Results: FAZ area was 0.42±0.03 mm2 in group A and 0.28±0.03 mm2 in group B (p<0.05). SCP VD was 11.4±3.1% in group A and 25.4±2.5% in group B (p<0.05). DCP VD was 22.3±1.1% in group A and 39.2±3.5% in group B (p<0.05). Choriocapillaris VD was 51.2±1.1% in group A and 63.1±1.2% in group B (p<0.05). Correlations between ocular parameters and ejection fraction (EF) were revealed (BCVA: r=0.61, p<0.05; MS: r=0.68, p<0.05; CMT: r=-0.72, p<0.05; FAZ: r=-0.73, p<0.05; SCP VD: r=0.82, p<0.05; DCP VD: r=0.81, p<0.05; choriocapillaris VD: r=0.76, p<0.05). Conclusions: in patients with hypertension and CHD with coronary artery stenosis, significant (p<0.05) reduction in BCVA, MS, SCP VD, DCP VD, and choriocapillaris VD and increase in CMT and FAZ area were detected compared to healthy individuals. Additionally, strong correlations between ocular parameters (FAZ, SCP VD, DCP VD, and choriocapillaris VD) and EF (p<0.05) were identified. OCTA may be recommended to monitor fundus vessels in hypertension and CHD as an effective noninvasive valuable diagnostic tool to verify hypertension and CHD. Keywords: hypertension, coronary heart disease, coronary artery stenosis, hypertensive retinopathy, foveal avascular zone, vessel density, optical coherence tomography angiography. For citation: Moshetova L.K., Vorobyeva I.V., Dgebuadze A. et al. Ophthalmological monitoring in patients with hypertension and coronary heart disease. Russian Journal of Clinical Ophthalmology. 2021;21(2):51–57. DOI: 10.32364/2311-7729-2021-21-2-51-57.